Study on main failure modes of multiple-holes structures based on branch-bound method - XIE, Wei; ZHANG, Yadan; MA, Zehua; FENG, Jinrong; WU, Yu (Xibei Gongye Daxue Xuebao, 2022)
Aiming at the typical five-hole structure on the aircraft skin, combined with the failure criterion of multi crack structure and considering the random factors affecting the residual life distribution of multiple crack structure, this paper applies the branch and bound algorithm to the screening of the main failure modes of typical five-hole structure, and gives the specific screening steps. The residual life of the structure is predicted by Franc3D crack propagation software, and the life interference model is established. Finally, the residual life distribution curve of the five-hole structure is formed to complete the screening of its main failure modes. The results show that the efficiency of using the algorithm to screen the main failure modes of the structure has been improved by 77.2%, and the error between the corresponding median life and that before screening is about 12%, indicating that the result of screening the main failure modes of the structure by the algorithm is more accurate. Compared with the existing test results, the median life predicted by the life distribution is more conservative and has certain reliability and accuracy. This method has certain reference significance for the evaluation of the safe life of this multi-holes structure. 针对飞机蒙皮上典型的五孔结构, 结合多裂纹结构失效判据, 考虑影响多裂纹结构剩余寿命分布的随机因素, 将分枝-约界算法应用于典型五孔结构主要失效模式筛选工作, 并给出具体的筛选步骤。通过Franc3D裂纹扩展软件预测结构剩余寿命, 建立寿命干涉模型, 最终形成五孔结构的剩余寿命分布曲线, 完成其主要失效模式的筛选。结果表明: 利用该算法对结构主要失效模式的筛选与简单的穷举法相比计算量减少了77.2%, 对应中值寿命与筛选前误差在12%左右, 表明该算法筛选结构主要失效模式结果较为准确; 与已有的试验结果相比, 用该寿命分布预测的中值寿命较为保守, 具有一定的可靠性和准确性。该方法对于此结构安全寿命的评估具有一定的借鉴意义。